Analysis Implementation of The Project Management Tools and Techniques PT. XYZ in Indonesia - Maulana Mufti Muhamamd; Budi Santosa (Institut Teknologi Sepuluh Nopember, 2019)
The level of business competition of an organization at this time is increasingly high. This is caused by economic factors and the presence of new competitors. Many organizations do not have the ability to deal with these conditions. Management of innovation and improvement that is limited by time, cost and quality are referred to as project management. Many methods, techniques, and tools have been developed, covering all aspects of project management from start to finish. If project management practices are implemented correctly, it allows for increased efficiency and productivity. In this study, how project management is implemented by evaluating the use of project management tools and effectiveness in supporting projects that run in the organization of PT. XYZ. This is done by distributing questionnaires to 30 respondents involved in the project that was carried out in 2018 to the present. The analytical method used is descriptive analysis and inferencing using SPSS used to determine the use of tools and project management techniques. Results in this study project management tools and techniques most often used by PT XYZ are progress reports, activity lists, and project charter. From the position positional factors and managed project costs factors are have significant value that affects the use of project management tools and techniques at PT XYZ in Indonesia